Species diversity, population structure, and regeneration status of trees in Fakim Wildlife Sanctuary, Nagaland, Northeast India - Aosanen Ao; Sapu Changkija; S. K. Tripathi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ao A, Changkija S, Tripathi SK. 2020. Species diversity, population structure, and regeneration status of trees in Fakim Wildlife Sanctuary, Nagaland, Northeast India. Biodiversitas 21: 2777-2785. The plant species composition and diversity represent the overall health of the forest ecosystems and provide useful insight on forest conservation, and the species regeneration is important in assessing the potential of the forests to serve the society on sustained basis. This present study aimed to assess the species diversity, population structure, and regeneration status of the trees in temperate forest of Fakim Wildlife Sanctuary, Nagaland, Northeast India. Tree species composition, population structure and regeneration status were analyzed by randomly establishing eight plots of 0.1 ha within the sanctuary. Density, basal area, abundance, evenness, and other diversity indices were calculated for mature trees with girth at breast height (GBH) ? 30 cm. A total of 60 tree species belonging to 40 genera and 27 families were recorded. The most dominant families recorded were Lauraceae and Rosaceae. The total tree density recorded from the forest was 432.5 individuals ha-1 with a basal area 42.8 m2 ha-1. Cinnamomum zeylanicum and Lithocarpus pachyphyllus had the highest density with 17.58 individuals ha-1 and Lithocarpus pachyphyllus had the highest basal area with 2.64 m2 ha-1. The species with the highest IVI was Betula alnoides (17.13). Girth class of 30-60 cm had the highest density and basal area with 280 individuals ha-1 and 20.7 m2 ha-1. The diversity indices such as Shannon-Wiener index, Simpson index, Pielou evenness index, and Margalef species richness index were 3.90, 0.93, 0.92, and 11.59, respectively in the wildlife sanctuary. The present study showed that 41% of tree species exhibited good regeneration status, 31% as fair regeneration, 8% as poor regeneration and 20% had no regeneration. The present data will be useful to understand the current status of tree species and will serve as baseline information to the forest department, policymakers and conservationists to develop management plans for the conservation of priority species in the area.